The Interrelationship between Type 2 Diabetes Mellitus, Functional Gastrointestinal Disorders, and Polycystic Ovary Syndrome in Reproductive Age Women - Mujeeb-Ur-Rehman Abro, Mahesh Kumar Wadhwa, Sania, Hinan Saeed Noonari, Ghulam Fatima, Yasmeen Khatoon, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Type 2 diabetes mellitus, polycystic ovary syndrome and functional gastrointestinal disorders are highly prevalent in reproductive-age women and share overlapping risk factors such as insulin resistance, obesity, and hormonal dysregulation. Objectives: To evaluate the prevalence and associations of polycystic ovary syndromes and functional gastrointestinal disorders in reproductive-age women with Type 2 diabetes mellitus, and to identify independent predictors of functional gastrointestinal disorders in this population. Methodology: This cross-sectional analytical study was conducted at Department of Diabetes & Endocrinology and Obstetrics & Gynaecology, Shaheed Mohtarma Benazir Bhutto Medical University Larkana from 1st April 2023 to 30th September 2023. Two hundred and twenty reproductive-age women with type 2 diabetes mellitus were included in the study. Polycystic ovary syndrome was diagnosed using the Rotterdam criteria, and functional gastrointestinal disorders were identified according to Rome IV guidelines. Clinical, demographic, and metabolic parameters were recorded. Results: The mean age of participants was 31.8±6.4 years, mean body mass index was 28.3±4.7 kg/m², and mean duration of diabetes was 5.2±3.1 years. Polycystic ovary syndrome was diagnosed in 82 women (37.3%), and functional gastrointestinal disorders were present in 94 women (42.7%), with irritable bowel syndrome being the most common subtype (20.9%). Women with functional gastrointestinal disorders had higher body mass index (29.5±4.9 vs. 27.4±4.3, p=0.003), longer duration of diabetes (6.1±3.4 vs. 4.6±2.9 years, p=0.001), and higher HbA1c levels (8.1±1.4 vs. 7.6±1.2, p=0.01). Logistic regression identified polycystic ovary syndrome (OR 2.15, 95% CI: 1.28–3.64, p=0.004), body mass index ≥28 kg/m² (OR 1.87, 95% CI: 1.12–3.12, p=0.016), and diabetes duration ≥5 years (OR 2.03, 95% CI: 1.21–3.41, p=0.007) as independent predictors of functional gastrointestinal disorders. Conclusion: Functional gastrointestinal disorders are highly prevalent in reproductive-age women with type 2 diabetes mellitus and are strongly associated with polycystic ovary syndrome, obesity, and longer diabetes duration. The coexistence of type 2 diabetes mellitus, polycystic ovary syndrome, and functional gastrointestinal disorders represents a compounded health burden, underscoring the need for integrated multidisciplinary management strategies to improve reproductive, metabolic, and gastrointestinal outcomes. Keywords: Type 2 diabetes mellitus, Polycystic ovary syndrome, Functional gastrointestinal disorders, Irritable bowel syndrome